2023
DOI: 10.3390/jfb14090450
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable, Green-Processed, Ag-Nanoparticle-Incorporated Eggshell-Derived Biomaterial for Wound-Healing Applications

Rosemond A. Mensah,
Federico Trotta,
Emily Briggs
et al.

Abstract: The eggshell membrane (ESM) is a natural biomaterial with unique physical and mechanical properties that make it a promising candidate for wound-healing applications. However, the ESM’s inherent properties can be enhanced through incorporation of silver nanoparticles (AgNPs), which have been shown to have antimicrobial properties. In this study, commercially produced AgNPs and green-processed AgNPs were incorporated into ESM and evaluated for their physical, biological, and antimicrobial properties for potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…[108] The same properties were confirmed by Tian et al, whose research confirmed the reduction of fibrogenic cytokines that initiate inflammation in the wound, [109] or Mensah et al, who combined Ag NPs into one material with eggshell membrane, the developed material, due to its properties, can be used as a potential skin dressing used in the treatment of wounds. [110] Another example of a nanocomposite that has a place as a potential wound-healing accelerator is chitosan and Ag NPs (Chi/Ag-NP). Studies to confirm the above use were carried out on the human fibroblast cell line.…”
Section: Application In Wound Treatmentmentioning
confidence: 99%
“…[108] The same properties were confirmed by Tian et al, whose research confirmed the reduction of fibrogenic cytokines that initiate inflammation in the wound, [109] or Mensah et al, who combined Ag NPs into one material with eggshell membrane, the developed material, due to its properties, can be used as a potential skin dressing used in the treatment of wounds. [110] Another example of a nanocomposite that has a place as a potential wound-healing accelerator is chitosan and Ag NPs (Chi/Ag-NP). Studies to confirm the above use were carried out on the human fibroblast cell line.…”
Section: Application In Wound Treatmentmentioning
confidence: 99%
“…While chemical and physical methods required toxic reducing and stabilising agents, biological "green" procedures only involve the use of natural and eco-friendly stabilising and reducing agents [77], which confer higher stability and unique biocompatibility key aspects during the bionanocomposites' biodegradation process [108]. Their enhanced stability avoids particle aggregation and the loss of colloidal behaviour responsible for their possible toxicity in the environment, contributing to AgNPs' positive effects on plants and lower toxicity [119,120]. Moreover, non-biodegradable stabilizing agents commonly exploited through chemical and physical methods may enhance the AgNPs' environmental toxicity, supporting the necessity of the development of green methods for metallic nanoparticles [121].…”
Section: Agnps Environmental Considerationsmentioning
confidence: 99%
“…This innovative approach holds great potential for advancing materials with improved antimicrobial characteristics and expanded versatility. Silver nanoparticles (AgNPs), in particular, have gained attention for their strong antimicrobial properties [28][29][30][31]. These nanoparticles exhibit a high surface area and unique physicochemical characteristics that enable them to effectively inhibit the growth of bacteria, fungi, and other harmful microorganisms in food, such as Escherichia coli (E. Coli), Enterococcus faecalis, and Staphylococcus aureus, when incorporated into packaging materials ranging from rigid plastics polyethylene (PET) [32], flexible low-density polyethylene (LDPE) [33], paper-based materials, and biopolymers [34].…”
Section: Introductionmentioning
confidence: 99%